Pulmonary Lymphangioleiomyomatosis and Extra-Pulmonary Lymphangioleiomyomas in Postmenopausal Women (Global Journal of Medical Research, 2020)
Lymphangioleiomyomatosis (LAM) is a rare disorder of unknown cause characterized by progressive cystic destruction of the lung, lymphatic abnormalities and abdominal tumors. It occurs almost exclusively in women of fertile age due to a hormonal influence, for this reason it is extremely rare in post-menopausal patients. While LAM is a systemic disease, the main manifestations are pulmonary. Lymphangioleiomyomas are larger cystic masses; these most commonly occur in the abdomen, retroperitoneum and pelvis but occasionally in the mediastinum and neck. In the cases of older women the disease presents a similar clinical manifestation than younger's female, with the exception that the clinical course is benign and longer.
Keywords: Lymphangioleimyomatosis; mediastinal lymphangioleiomyomas; postmenopausal women; cystics lungs